CORPORATE SOCIAL RESPONSIBILITY PROGRAM IMPACTS THE CUSTOMER LOYALTY OF BANK RAKYAT INDONESIA BRANCH MANADO - Talumepa, Gary C.; Mekel, Peggy A. (Universitas Sam Ratulangi, 2014)
The successfulness of a firm is not just determined by its financial metrics. Corporate social responsibility (CSR) lately becomes one major concern in businesses which are indicating whether the company goes well or not. CSR program is the major concern that will be elaborate in this research. The aim of this research is to know if CSR programs of BRI branch Manado impact its customer loyalty and what are the factors that influence. This study is conducted by quantitative technique with associative type of research. Populations in this research are exactly the customers of BRI in Manado. Total of 100 respondents are being sampled. Purposive sampling is used in this research. CSR and customer loyalty theories are the supporting theories in this research. The result shows that CSR significantly impact customer loyalty through three factors that linked between these two variables. BRI management suggested that to develop CSR programs in order to maximizing profit by gaining greater customer loyalty, and also help to improve societal well-being. Keywords: corporate social responsibility, customer loyalty